The life and work of G.B.A. Gerdener with special reference to his contributions to Afrikaner identity formation and the racial discourse in South Africa from 1925 to 1950 - Pienaar, Jacques (Stellenbosch : Stellenbosch University, 2020)
Thesis (MTh)--Stellenbosch University, 2020.